Common variants of APOE are associated with anti-epileptic drugs resistance in Han Chinese patients. (2nd January 2017) - Gong, Jiao-E; Qu, Jian; Long, Hong-Yu; Long, Li-Li; Qu, Qiang; Li, Xiang-Ming; Yang, Li-Ming; Xiao, Bo
Abstract : Purpose/aim of the study : Apolipoprotein E ( APOE ) has been implicated as one of the susceptibility genes for some subtypes of epilepsy and may be related to anti-epileptic drugs resistance. The purpose of this study was to investigate the possible association between APOE variants and the anti-epileptic drugs resistance in Chinese population. Materials and methods : APOE gene rs429358 and rs7412 variants were genotyped for ϵ 2, ϵ 3, ϵ 4 alleles using amplification refractory mutation system in 480 subjects including 207 anti-epileptic drugs-resistant patients and 273 drug-responsive patients. Results : We found that the frequency of APOE gene rs429358 C allele in the drug resistant patients is higher than that in the drug-responsive patients (14.98% vs . 10.1%, OR = 1.25[1.02 − 1.52], p  = 0.017). Moreover, according to the two variants, we analyzed the distributions of − ϵ 4 and + ϵ 4 alleles of APOE gene and found that there were higher frequencies of + ϵ 4 allele in drug-resistant epileptic patients than that in drug-responsive patients (31.8% vs . 13.2%, OR = 1.15[1.05 − 1.25], p  = 0.002). Conclusions : Our study demonstrated that APOE rs429358 variant C allele and ϵ 4 allele were associated with the anti-epileptic drugs resistance in Han Chinese patients.